Visualization in modern cartography - MacEachren, Alan M., 1952-; Taylor, D. R. F. (David Ruxton Fraser), 1937- (Modern cartography, 1994)
Visualization in Modern Cartography explores links between the centuries-old discipline of cartography and today's revolutionary developments in scientific visualization. The book has three main goals: (1) to pass on design and symbolization expertise to the scientific visualization community - information that comes from centuries of pre-computer <Q>visualization</Q> by cartographers, and their more recent experiences with computerizing the discipline; (2) to help cartographers cope with the dramatic shift from print cartography to a dynamic virtual cartography for which their role is changing from that of map designer to one of spatial information display (and/or interface) designer; (3) to illustrate the expanded role for cartography in geographic, environmental, planning, and earth science applications that comes with the development of interactive geographic visualization tools. To achieve these goals, the book is divided into three parts. The first sets the historical, cognitive, and technological context for geographic/cartographic visualization tool development. The second covers key technological, symbolization, and user interface issues. The third provides a detailed look at selected prototype geographic/cartographic visualization tools and their applications.